Meanings of intrafamily violence experienced in childhood/adolescence present in the discourses of men - Júlia Renata Fernandes de Magalhães; Álvaro Pereira; Nadirlene Pereira Gomes; Andrey Ferreira da Silva; Fernanda Matheus Estrela; Milena Arão da Silva Oliveira; Moniky Araújo da Cruz
ABSTRACT Objective: to unveil the meanings of intrafamily violence experienced in childhood and/or adolescence by men under legal proceedings due to conjugal violence. Method: a qualitative research, based on Thematic Oral History and supported by Symbolic Interactionism. Participants were men under legal proceedings due to domestic violence who had experienced or witnessed intrafamily violence in childhood and/or adolescence. Results: the speeches revealed that the intrafamily violence experienced in childhood and/or adolescence was signified as an educational method. The aggressions committed by parents were only perceived as acts of violence in situations considered extreme, such as in cases of using a firearm, handcuffs, and rope. Final considerations: considering that the meanings direct human conduct and that they are subject to modification depending on social interactions built throughout life, it is believed that educational strategies that encourage the redefinition of violence can be effective in facing this problem.